2020
DOI: 10.1177/0272684x20967602
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Patient Trust in Doctors: A Cross-Sectional Survey of Out-Patient Departments in Fiji

Abstract: Background Despite evidence on the positive impact of trust in a doctor-patient relationship on health outcomes, there are limited studies conducted in Pacific Island Countries including Fiji. This study was conducted to assess the current level of patient trust in doctors and investigate its determinants in Fiji. Method: A random sample of 410 participants attending the outpatient services completed the self-administered structured questionnaire. The response rate was 91% (N=375) and data was analyzed using d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Trust in doctors is relatively high in both age groups when compared to the under 65 age group, because they are more positive about doctors’ attitudes towards finding information online and less likely to search for information online when seeing a doctor. The higher general level of trust in doctors among older people is in line with the results of other international studies [ 36 38 ], indicating that the primary “source” or reference point for this age group is face-to-face contact with the doctor and that digital solutions are of secondary importance. The different levels of eHealth literacy may also play a role: the aforementioned study of older people in the US [ 33 ] highlights that fewer of those who preferred to rely on their doctor’s knowledge for medical decision making (38.3%) had high eHealth literacy than those who did not prefer to rely on their doctor’s knowledge (58.6%).…”
Section: Discussionsupporting
confidence: 86%
“…Trust in doctors is relatively high in both age groups when compared to the under 65 age group, because they are more positive about doctors’ attitudes towards finding information online and less likely to search for information online when seeing a doctor. The higher general level of trust in doctors among older people is in line with the results of other international studies [ 36 38 ], indicating that the primary “source” or reference point for this age group is face-to-face contact with the doctor and that digital solutions are of secondary importance. The different levels of eHealth literacy may also play a role: the aforementioned study of older people in the US [ 33 ] highlights that fewer of those who preferred to rely on their doctor’s knowledge for medical decision making (38.3%) had high eHealth literacy than those who did not prefer to rely on their doctor’s knowledge (58.6%).…”
Section: Discussionsupporting
confidence: 86%
“…and that he is aware of the duration, timing, and adequate interpretation provided to them by medical care providers in general [30]. He communicates verbally and nonverbally with the doctor by showing sympathy and acting politely, listening well, and with patients [1]. In the same direction, it was also defined as the extent to which the medical service provider actively listened to patients' concerns, and explained things in ways that could be understood and treated with kindness, appreciation, and respect [31].…”
Section: Factors Of Trust 221 Communicationmentioning
confidence: 99%
“…Trust represents the beating heart of the relationship between the medical provider and the patients and the basis and key to its overall success [1]. Related studies have shown that trust has many positive benefits among them, it helps to improve the adherence process and follow-up medical treatment and enhances the process of communication between them and continuity of care with the same doctor or medical provider [2].…”
Section: Introductionmentioning
confidence: 99%
“…19 In addition, quantities of research have shown that physicians' verbal and non-verbal communication skills such as assurance of treatment, giving more information and showing caring behaviors (eg, displaying empathy and intent listening) are beneficial in establishing TIP. 12,20,21 However, studies using nationally representative data about TIP in China are still lacking. Most of the previous studies in China about TIP were based on some specific provinces, cities or even hospitals and their findings were mixed.…”
Section: Introductionmentioning
confidence: 99%